Nucleus‐Targeting Carbon Quantum Dots Assembled with Gambogic Acid via π–π Stacking for Cancer Therapy. Issue 1 (15th November 2022) - Liu, Shanshan; Wang, Jianfeng; Li, Haiguang; Xu, Chen; Guo, Yimin; Bao, Xiaotong; Guan, Shaokang; Liu, Hairong; Zhang, Tao
Abstract: Chemotherapy combined with nanocarriers has received increased attention as a thriving strategy for tumor therapy. However, drug resistance (DR), poor circulation, and retention in cells are the main challenges of this therapy. Herein, a novel strategy is developed to target drug delivery via π–π stacking interactions to overcome DR and short circulation and retention in cells. Carbon quantum dots (CDs) and gambogic acid (GA) are assembled via a π–π stacking interaction, which increases the drug‐loading capacity of CDs as well as the circulation and retention of GA‐loaded CDs (CDs/GA). CDs/GA significantly inhibit cell proliferation because CDs enter the nucleus and avoid drug pump recognition. GA released from CDs/GA promotes apoptosis by inducing the production of reactive oxygen species via the mitochondrial pathway. As a result, the delivery system of CDs/GA via π–π stacking displays a significant therapeutic effect on hepatoma (HepG2) and cervical cancer (HeLa) cells. The mechanisms of DR and induction of apoptosis are further investigated. The results suggest that chemotherapy combined with CDs can facilitate the targeting of the nucleus, thereby inducing apoptosis via the mitochondrial pathway. Abstract : A novel strategy of carbon quantum dots (CDs) connected with gambogic acid (GA) via a π–π stacking interaction is developed to achieve a high drug loading, target drug delivery for overcoming DR, and short circulation and retention. Moreover, CDs/GA promote apoptosis by inducing the production of reactive oxygen species and via the mitochondrial pathway.